Jestem stąd, więc. . . - poczucie tożsamości mieszkańcow ziemi lubińskiej i polkowickiej = I am from here, so. . . - identity awareness among the inhabitants of the Lubin and Polkowice regions - Techmańska, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author analyses the identity of the inhabitants of the region of Lubin and Polkowice and singles out the elements that could have influenced it. In formulating the final conclusions a questionnaire was used where the respondents reflected on their relations with the place they live in, and specified if those relations had only psychological background or were based on the historical or anthropological and ethnographical factors as well. The question if the Lubinians and Polkowicians wish to initiate the local and regional activities was also asked.
Keywords: tożsamość regionalna; Polkowice; Lubin